Competitive state anxiety and performance among Malaysian athletes from the view of multidimensional anxiety theory / Vincent A. Parnabas, Yahaya Mahamood and Kwame Ampofo-Boateng - Parnabas, Vincent A.; Mahamood, Yahaya; Ampofo-Boateng, Kwame (Faculty of Sports Science and Recreation, 2013)
The Multidimensional Anxiety theory examines the relationship between anxiety and performance. It is the first theory that explains that both cognitive and somatic components play an important role on performance. Cognitive anxiety is the mental component of anxiety and somatic anxiety refers to a person’s perceived changes in her or his physiological. The theory hypothesizes a powerful negative linear relationship between cognitive state anxiety and performance and a less powerful, inverted U relationship between somatic anxiety and performance. The theory states that the increases of cognitive and somatic anxiety will deteriorate an athlete’s performance. However, previous research had showed inconsistent results. Therefore, this research examines the effect of cognitive and somatic anxiety on performance among Malaysian athletes. The sample consisted of 902 athletes, consisting of national (N=53), state (N=395), district (N=120), university (N=211), and school athletes (N= 123). The sample was drawn from among athletes who competed in three big sport events of Malaysia, MASUM (Universities Sports Competition), MSSM (Schools Sport Competition) and Sukan Olimpik Muda (Young Olympic Athletes Competition).The instrument used for the study comprised of a 27-item Competitive State Anxiety Inventory–2, consisting of cognitive and somatic component. The result has received support from the Multidimensional Anxiety theory, that the increased level of cognitive and somatic anxiety deteriorated athletes’ performance. Coaches, sport psychologists and counsellors can use this research to reduce the cognitive and somatic anxiety to increase athletes’ performance.